Endotoxemic shock from urinary calculus dog - Rispoli, V. F. P.; Lopes, R. D.; Dullius, J. L.; Ruiz, V. L. A. (Scientific Electronic Archives, 2018)
This study aims to present a case of a dog of the Bichon Frizé breed, male that arrived on the 06/08/2015 at Provet - Moema Pathology Service for a necropsy. According to the history provided by the owner, four days before the death of the animal, the dog began to limp during the tour, presented episodes of limping for two consecutive days, and had a cardiac arrest. After receiving medications he had three more episodes of emesis and had a new cardiorespiratory arrest that led him to death. On the history of the animal, four years before the death the animal had its urinary bladder ruptured (S.I.C.). It is believed that the animal has seen as the bane endotoxemic shock generated by necrotizing and hemorrhagic cystitis with chronic active vasculitis. Â